Cardiac ultrasonography over 4G wireless networks using a tele‐operated robot. Issue 3 (28th September 2016) - Avgousti, Sotiris; Panayides, Andreas S.; Jossif, Antonis P.; Christoforou, Eftychios G.; Vieyres, Pierre; Novales, Cyril; Voskarides, Sotos; Pattichis, Constantinos S.
Abstract : This Letter proposes an end‐to‐end mobile tele‐echography platform using a portable robot for remote cardiac ultrasonography. Performance evaluation investigates the capacity of long‐term evolution (LTE) wireless networks to facilitate responsive robot tele‐manipulation and real‐time ultrasound video streaming that qualifies for clinical practice. Within this context, a thorough video coding standards comparison for cardiac ultrasound applications is performed, using a data set of ten ultrasound videos. Both objective and subjective (clinical) video quality assessment demonstrate that H.264/AVC and high efficiency video coding standards can achieve diagnostically‐lossless video quality at bitrates well within the LTE supported data rates. Most importantly, reduced latencies experienced throughout the live tele‐echography sessions allow the medical expert to remotely operate the robot in a responsive manner, using the wirelessly communicated cardiac ultrasound video to reach a diagnosis. Based on preliminary results documented in this Letter, the proposed robotised tele‐echography platform can provide for reliable, remote diagnosis, achieving comparable quality of experience levels with in‐hospital ultrasound examinations.